Loyalitas Tenaga Pendidik: Faktor Penentu dan Implikasinya pada Sekolah di SMPN 4 Satu Atap Karangjambu - Isnaini Nurul Hidayati; Muh. Hanif (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research aims to analyze the factors that influence the loyalty of teaching staff and their implications for the development of SMPN 4 Satu Roof Karangjambu. The research method used is a qualitative approach with case studies, which involves collecting data through interviews and observations of teaching staff and school principals. The research results show that organizational climate, job satisfaction, and compensation are the main factors influencing teaching staff's loyalty. A positive organizational climate, supported by open communication and collaboration between school principals and teachers, significantly increases loyalty. Compensation has met standards. However, there is still hope that there will be an increase in compensation. However, the working atmosphere and development opportunities remain dominant in increasing loyalty. Job satisfaction has also proven significant, with teaching staff feeling valued and given space to innovate. Although distance and policy changes are external factors that need to be considered in transfers, these do not significantly influence educators' decisions. These findings indicate that school management must pay attention to good interpersonal relationships and professional development policies to increase loyalty. The prospect of this research is to explore further the relationship between organizational culture and loyalty and assess external factors in schools with limited facilities.